Frozen thawed embryo transfer cycles; A comparison of pregnancy outcomes with and without prior pituitary suppression by GnRH agonists: An RCT - Alamtaj Samsami; Zohre Chitsazi; Golnaz Namazi (Shahid Sadoughi University of Medical Sciences, 2018)
Background: To perform an in-vitro fertilization cycle, pretreatment with gonadotropin-releasing hormone (GnRH) agonist is widely used as a part of controlled ovarian hyper-stimulation protocols to prevent endogenous luteinizing hormone surge and spontaneous ovulation. GnRH agonist pretreatment is relatively costly and there is a risk of hypo estrogenic side effect. It would also lengthen the preparation period until pituitary desensitization occurs. Objective: Our study is aimed at evaluating the pregnancy outcome rate of frozen thawed embryo transfer with and without GnRH agonists pretreatment. Materials and Methods: Women with documented infertility who were candidate for frozen thawed embryo transfer were recruited and randomly assigned to two groups. In group A (n=100), patients received GnRH agonist, Buserelin, to induce pituitary desensitization prior to endometrial preparation and embryo transfer. Individuals in group B (n=100) received steroid manipulation without prior down-regulation of the pituitary. Chemical pregnancy, implantation rate, clinical pregnancy and ongoing pregnancy were measured and statistically compared between the two groups. Results: None of the outcome measures including clinical and chemical pregnancy rates, implantation rate, and ongoing pregnancy rate showed significant difference between the two groups. Similarly, the rate of miscarriage did not vary between the two groups. Conclusion: In this study, we found that removing the GnRH agonists pretreatment from the programmed cycles did not negatively influence the pregnancy outcome or implantation rate. Moreover, it will cause a considerable reduction in cost of assisted reproductive technology as well as adverse effects related